Option C: -3 is the average rate of change between
and ![x=1](https://tex.z-dn.net/?f=x%3D1)
Explanation:
The formula to determine the average rate of change is given by
Average rate of change = ![\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
We need to find the average rate of change between
and ![x=1](https://tex.z-dn.net/?f=x%3D1)
Thus, from the table, we have,
, ![y_1=5](https://tex.z-dn.net/?f=y_1%3D5)
, ![y_2=-1](https://tex.z-dn.net/?f=y_2%3D-1)
Thus, substituting these values in the formula, we get,
Average rate of change = ![\frac{-1-5}{1+1}](https://tex.z-dn.net/?f=%5Cfrac%7B-1-5%7D%7B1%2B1%7D)
![=\frac{-6}{2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-6%7D%7B2%7D)
![=-3](https://tex.z-dn.net/?f=%3D-3)
Thus, the average rate of change between
and
is -3.
Hence, Option C is the correct answer.
Answer:
ىر سيىخرسىي ىتسيرىتسهارسيخهكتر يسرلاتزسنيى يتريزىيسئرتسئرة سينرةظسئر سظرى ئمرىسنرمسيىمر سئرىسئنرتىئسر ؟
Answer:
a, also there is a calculator on google for this, if you have any more!
Step-by-step explanation:
The output k at input t = -7 is -89
Step-by-step explanation:
In order to find the value of a expression on given number, we put the number in given expression in place of independent variable
So,
Given expression is:
![k = 10t-19](https://tex.z-dn.net/?f=k%20%3D%2010t-19)
It is given that the value of t has to be -7
so putting t=-7 in the expression
![k = 10(-7)-19\\k = -70-19\\k = -89](https://tex.z-dn.net/?f=k%20%3D%2010%28-7%29-19%5C%5Ck%20%3D%20-70-19%5C%5Ck%20%3D%20-89)
Hence,
The output k at input t = -7 is -89
Keywords: Expressions, input, output
Learn more about expressions at:
#LearnwithBrainly
So the unit rate would just be the numbers all added up